2005
DOI: 10.1039/b412062k
|View full text |Cite
|
Sign up to set email alerts
|

The mineral phase in the cuticles of two species of Crustacea consists of magnesium calcite, amorphous calcium carbonate, and amorphous calcium phosphate

Abstract: The cuticules (shells) of the woodlice Porcellio scaber and Armadillidium vulgare were analysed with respect to their content of inorganic material. It was found that the cuticles consist of crystalline magnesium calcite, amorphous calcium carbonate (ACC), and amorphous calcium phosphate (ACP), besides small amounts of water and an organic matrix. It is concluded that the cuticle, which constitutes a mineralized protective organ, is chemically adapted to the biological requirements by this combination of diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
121
1
4

Year Published

2006
2006
2013
2013

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 140 publications
(137 citation statements)
references
References 39 publications
11
121
1
4
Order By: Relevance
“…At intra-molt stage, this content increases immediately to approximately 66 wt % and then decreases to Ϸ35 wt % and approximately 25 wt % in stages 3 and 4, respectively. The organic content in inter-molt is only Ϸ19 wt %, which is close to a previously reported value, 13 wt % (26). The maximum in organic component coincides with the initiation of phase transformation.…”
Section: Resultssupporting
confidence: 64%
“…At intra-molt stage, this content increases immediately to approximately 66 wt % and then decreases to Ϸ35 wt % and approximately 25 wt % in stages 3 and 4, respectively. The organic content in inter-molt is only Ϸ19 wt %, which is close to a previously reported value, 13 wt % (26). The maximum in organic component coincides with the initiation of phase transformation.…”
Section: Resultssupporting
confidence: 64%
“…Both experimental and computational investigations in the literature provided evidence indicating that calcite crystals with low concentrations of Mg are stable in structure (19,(69)(70)(71); these studies, however, predicted that high concentrations of Mg (≥ ∼50 atom %) may prevent crystal formation because of the increasing structural stiffness and distortion resulting from the random Mg substitution of Ca (72,73). Recent studies (73) using computational methods reported that substituting Ca by Mg in calcite crystals can alter the cation-C and the cation-cation interatomic distances significantly and cause local tilt of the CO 3 2− groups while maintaining the C-O (within the CO 3 2− ) and the cation-O bond lengths constant.…”
Section: Resultsmentioning
confidence: 99%
“…Both structural organization and type and degree of mineralization observed in cuticle from different Crustacea species have been positively correlated to ecophysiological adaptations like defensive strategies (Becker et al, 2005;Hild et al, 2008), special habitats (Hild et al, 2008;Seidl et al, 2011) or economy of material and thus energy . The organization of the cuticle forming the dorsal carapace of the crab C. pagurus suggests a high resistance against mechanical loads, especially loads applied in the direction perpendicular to the surface.…”
mentioning
confidence: 99%